Exploring strategies in developing a consistent branding for Tulunan United Women?s Initiative for Development (TUWID) Organization in Tulunan, North Cotabato - Panes, Kristine Ghale M.
Branding strategies have evolved significantly over the years, from merely creating brand images to being cultural agents. Culture and brand became intertwined, giving rise to what is called "brand culture", an organization's innate core values (Bhasin, 2018). Some companies, despite having a brand identity and an online presence, lack a consistent brand culture, making them less competitive in the market. This research explores strategies in developing a consistent brand culture for the Tulunan Unified Women's Initiative for Development (TUWID) in Tulunan, North Cotabato, Philippines. It aims to provide insights and propose a creative brief to guide TUWID in establishing a consistent brand culture. It adopts concepts from cultural branding theory developed by Douglas Holt (2004) and systems theory as a theoretical framework and utilizes the Double Diamond Design Process Model for research design. A cultural audit is conducted to gain insights from the case organization through interviews and data analysis. The research findings highlight key themes such as respect, cooperation/unity, equality, women's empowerment, inclusivity, and a sense of identity. These themes serve as cultural codes for developing a comprehensive cultural branding strategy for TUWID. The findings of the study indicate that maintaining a consistent brand culture is essential to the growth and impact of TUWID in the community. The researcher suggests improving consistent branding and marketing strategies, designing training programs, incorporating a culturally sensitive approach, and evaluating the socioeconomic impact of TUWID's initiatives. This research contributes to TUWID?s brand culture development and supports the local community.